Collection of test for practical training in clinical neurology for practical employments for the students of the 4th course of II international faculty - Kozyolkin, O. A.; Vizir, I. V.; Sikorskay, M. V.; Козьолкін, Олександр Анатолійович; Візір, Ірина Володимирівна; Сікорська, Марина Володимирівна (Запорізький державний медичний університет, 2019)
Further progress of higher medical education requires implementing new forms of both teaching methods and knowledge control. These new forms intensify the learning process and develop student’s practical diagnostic. The training manual includes tests of private neurology, which are designed to help students in self-preparation for practical exercises students’ knowledge, their clinical thinking in seminars, tests, and neurological exam.